Detecção do vírus da cinomose canina por diferentes metodologias analíticas - Basso, Caroline Rodrigues [UNESP] (2015)
The canine distemper virus known as CDV, affects animals carnivorous order and is considered one of canine diseases more difficult to diagnose clinically, and may leading to the death about 85% of infected dogs. Currently, there are several techniques for the diagnosis of canine distemper among them stands out the ELISA methods, in situ hybridization, serological tests, fluorescence and PCR technique, however they may present lengthy results and a high cost. In recent years, the development of biosensors has been presented as an alternative to chemical and biochemical detection of several compounds showing high potential for application in clinical diagnostics. Thus, we developed an analytical methodology for the rapid diagnosis of canine distemper virus in real samples, with high viral load, using different techniques such as surface plasmon resonance (SPR), located surface plasmon resonance (LSPR), electrochemical impedance spectroscopy (EIS) and colorimetry